Laboratory Evaluation of Selected Animal Drawn Implement for the State of Meghalaya - Sahay, C S; Thomas, E V; Satapathy, K K; Kumar, Arvind (Journal of Agricultural Engineering, 2011)
In order to match commonly used animal drawn implement used in North Eastern Hilly (NEH) region with available animate power sources; local plough, ridger plough and mould board plough were tested in an indoor instrumented soil bin. Unit draft of soil was calculated using draft of implement and cross sectional area of furrow opened. There was increase of 21.3, 86.2 and 94.2 N draft in case of local plough, ridger and mould board plough, respectively, when the speed of operation was increased from 0.49 to 0.99 m/s.